Effects of the Rates of Application of Copper and Lead on Soil Microbial Activities - Faborode, Jumoke Olasumbo (2015)
The study assessed the effect of copper and lead application on microbial activities in the soil. It also determined their effect on microbial population and the concentration that is toxic to soil microorganisms. This was with a view to assessing the quantitative and qualitative effects of these metals on soil microorganisms.